1975
DOI: 10.1111/j.1365-2125.1975.tb00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the beta2‐adrenoceptor selectivity of rimiterol, salbutamol and isoprenaline by the intravenous route in man.

Abstract: 1The bronchodilating efficacy and the degree of 12-adrenoceptor selectivity of rimiterol, salbutamol and isoprenaline were determined in seven subjects who exhibited histamineinduced bronchoconstriction.2 Rimiterol, 0.5 (high dose) and 0.05 (low dose) ,ug kg min-', salbutamol, 0.3 and 0.03, g kg-l min-', isoprenaline, 0.05 and 0.005 gg kg-I min-and placebo were administered by a single intravenous injection over 6 min, and the protection against histamine-induced bronchoconstriction, changes in heart rate, pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…If the cat soleus muscle preparation is a predictive model for enhancement of physiological tremor in man, as has been suggested (Bowman & Nott, 1970) then all of the /3adrenoceptor agonists examined to date would be expected to enhance physiological tremor and cause bronchodilatation over the same dose-range when administered systematically. It is noteworthy that in the two studies reported in man in which this question has been examined in detail, the bronchodilator actions of salbutamol, terbutaline and rimiterol were accompanied by enhanced physiological tremor (Watson & Richens, 1974;Marlin & Turner, 1975). We therefore agree with the previous conclusions (Bowman & Nott, 1970;Bowman & Rodger, 1972) that it may prove impossible to separate the broncho-dilating and tremor-enhancing properties of /1adrenoceptor agonists except by giving the drugs by inhalation.…”
Section: Discussionsupporting
confidence: 89%
“…If the cat soleus muscle preparation is a predictive model for enhancement of physiological tremor in man, as has been suggested (Bowman & Nott, 1970) then all of the /3adrenoceptor agonists examined to date would be expected to enhance physiological tremor and cause bronchodilatation over the same dose-range when administered systematically. It is noteworthy that in the two studies reported in man in which this question has been examined in detail, the bronchodilator actions of salbutamol, terbutaline and rimiterol were accompanied by enhanced physiological tremor (Watson & Richens, 1974;Marlin & Turner, 1975). We therefore agree with the previous conclusions (Bowman & Nott, 1970;Bowman & Rodger, 1972) that it may prove impossible to separate the broncho-dilating and tremor-enhancing properties of /1adrenoceptor agonists except by giving the drugs by inhalation.…”
Section: Discussionsupporting
confidence: 89%
“…In view of this association of effects of sympathomimetic amines on the cat soleus and on slow motor units in man, the cat soleus preparation has been used to predict the tremorogenic activity of 0-adrenoceptor agonists in man. It is used in particular in the pre-clinical assessment of sympathomimetic bronchodilators, and its value in this respect has been substantiated by a correlation between the potencies of drugs in depressing the cat soleus (Bowman & Nott, 1970;Gwee et al, 1972;Houston & Rodger, 1974) and in causing tremor in man (Watson & Richens, 1974;Marlin & Turner, 1975). Because of its typical 0-adrenoceptor-mediated depressant action on the soleus, THP is thus likely to exert direct tremorogenic actions on muscle fibres of slow motor units in man.…”
Section: Discussionmentioning
confidence: 99%
“…However in one patient (Case 5) salbutamol by constant IV infusion was effective in restoring normal ventilation without the tachycardia invariably present with isoprenaline. When equivalent doses of isoprenaline and salbutamol IV in man are compared, the former is 5 times more potent as a bronchodilator, and has a 10 times greater effect on heart rate (Marlin and Turner, 1975). Salbutamol by constant IV infusion has therefore fewer cardiac side effects and is now our first choice f-stimulant.…”
Section: Discussionmentioning
confidence: 99%